Evaluación de especies forestales establecidas con fines de enriquecimiento y de sucesión natural nativas en bosque secundario pie montano de la microcuenca “El Padmi” Zamora Chinchipe - Luzón Guamán, Carlos Alberto (2023)
Deforestation has caused the progressive degradation and fragmentation of natural ecosystems; therefore, multiple efforts have been developed in order to restore the affected places with species that allow the restoration of some of the ecosystem services that were altered in the process of intervention in the natural ecosystem. However, due to the use of exotic species for forestry activities in restoration, native species have not been taken into account, which, due to their characteristics, are a better alternative for restoration. The purpose of this research was to contribute information that allows us to determine that the species that develop in the Piemontano forests of the Province of Zamora Chinchipe are an alternative for the restoration of deforested places. For this, two random plots were established adjacent to the enrichment area of 20 m × 20 m meters in the foothill secondary forest of the "El Padmi" Zamora Chinchipe hydrographic unit, where an inventory was carried out in order to obtain dasometric data and floristics of the natural forest and be able to compare them with the dasometric data obtained from the species used in the enrichment. Subsequently, the development of the DAP 1.30 m and the total height of the forest species were evaluated in 8 enrichment plots, of which six have an area of 300 m2 and two of 400 m2 at a distance between species of 5 m × 5 m, which were reforested with 20 and 25 individuals of three native species 18 years ago in the Piemontano secondary forest of the "El Padmi" hydrographic unit, province of Zamora Chinchipe. A unified double-entry table was created that was analyzed using the InfoStat student version program, where comparisons were developed with the Tukey test. Based on the results obtained, there is a significant difference between enrichment and forest regeneration in terms of growth in diameter, height, and volume, so it can be mentioned that the planting of native species as an enrichment is viable, given that natural regeneration alone does not develop adequately due to anthropic factors or vestiges of activities previously developed in the place. Keywords: Forestry, Dasometry, Growth, Statistical Comparison, Intervened Evaluation.